The physiological basis and clinical significance of lung volume measurements - Lutfi, Mohamed Faisal (Multidisciplinary Respiratory Medicine, 2019)
From a physiological standpoint, the lung volumes are either dynamic or static. Both subclasses are measured at different degrees of inspiration or expiration; however, dynamic lung volumes are characteristically dependent on the rate of air flow. The static lung volumes/capacities are further subdivided into four standard volumes (tidal, inspiratory reserve, expiratory reserve, and residual volumes) and four standard capacities (inspiratory, functional residual, vital and total lung capacities). The dynamic lung volumes are mostly derived from vital capacity. While dynamic lung volumes are essential for diagnosis and follow up of obstructive lung diseases, static lung volumes are equally important for evaluation of obstructive as well as restrictive ventilatory defects. This review intends to update the reader with the physiological basis, clinical significance and interpretative approaches of the standard static lung volumes and capacities.